An analysis of "in memoriam" - Waters, Elsie Lucile (My University, 1898)
Introduction: Rhythm is inherent in the human breast, and the universe is filled with it. The voices of nature greet us everywhere and their music is sweet. Be it rhythm in nature or in language, there is no power which appeals more strongly to the emotions. “Music,” says one, “is almost divine,” and there is music in poetry. It is those who have sung to the world the sweetest songs, who are remembered longest. Of these, there have been many, each great in his day, but above all for sweetness of song, and tender fathers, stands the name of Alfred Tennyson, whose life began at Lincolnshire England 1809. As will all great poets, his genius was inherited. Without attempting any review of his life or preparation for his calling, we go at once to his works of which there are many. Perhaps no other writer has contributed as much to literature as did this one of England’s greatest poets.
Citation: Waters, Elsie Lucile. An analysis of "in memoriam". Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Rhythm; Music; Human; Poetry; Theses; Manuscripts (documents)